Study of Exclusive Breastfeeding Behavior for Toddlers aged 7-24 months - Bahar, Hartati; Vebyarti, Vebyarti (Universitas Islam Negeri Alauddin Makassar, 2023)
The target of at least 80% coverage of exclusive breastfeeding for infants aged 0-6 months is still difficult to achieve. This causes exclusive breastfeeding tends to decrease from year to year. This study aims to determine the behavior of exclusive breastfeeding in the working area of the Jati Raya Community Health Center, Kendari City. The method used in this study is a qualitative phenomenological approach. The research was carried out in the working area of the Jati Raya Health Center. Research informants were mothers who had babies aged between 7-24 months and stakeholders of the Exclusive Breastfeeding program at the Jati Raya Health Center. The sampling technique was carried out by purposive sampling. Data collection was carried out through in-depth interviews. In-depth interviews were conducted with 6 informants consisting of 6 mothers who had babies aged 7-24 months and 2 stakeholders of the Exclusive Breastfeeding program. Data analysis using Content Analysis. The results showed that the mother's behavior in exclusive breastfeeding was quite good. This happens because of the many influencing factors including attitudes, subjective norms (health workers, family support), perceptions of control and good intentions of mothers in giving exclusive breastfeeding to their babies. Conclusion: Attitudes, subjective norms and perceptions of behavioral control are collectively associated with behavioral intentions and intentions are direct antecedents of exclusive breastfeeding behavior. Suggestion: increasing the coverage of exclusive breastfeeding programs can be done by helping to improve positive attitudes, changing subjective norms to support exclusive breastfeeding, improving perceived behavioral control, and strengthening intentions to give exclusive breastfeeding